PREVALENSI TRICHUROSIS PADA SAPI POTONG DI KECAMATAN KASIMAN, KABUPATEN BOJONEGORO, JAWA TIMUR - Aji Winarso; Fadjar Satrija; Yusuf Ridwan (JURNAL KAJIAN VETERINER, 2019)
A cross-sectional studie was conducted to determine prevalence and risk factors of trichurosis in beef cattle in Kasiman Subdistrict, the regency of Bojonegoro. A total of 263 and 270 head of local beef cattle with various age were taken for fecal sample during dry season (August-October 2014) and wet season (February-March 2014), respectively. Feces were processed for McMaster’s method. The prevalences of trichurosis were 7.22% and 5.19% in the dry season and rainy season, respectively. Seasonal factors did not significantly affect the prevalence (p=0329). During the dry season and the rainy season, the prevalence between age groups and between the sexes did not show significant differences (p>0.05). However, young cattle had a tendency to be more susceptible than older age. Cattle of age >6-12 months were more likely four times get trichurosis than adult cows (> 2 years).